Socioeconomic development, family income, and psychosocial risk factors: a study of families with children in public elementary school Desenvolvimento socioeconômico, renda monetária familiar e fatores de risco psicossociais: um estudo com famílias da rede pública do ensino fundamental - Simone Gonçalves de Assis; Thiago Pires; Renata Pires Pesce; Joviana Quintes Avanci; Raquel V. C. Oliveira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
This article aims to evaluate the effects of Brazil's recent economic growth on the monetary income, consumption patterns, and risk exposures of families with children enrolled in the public elementary school system in São Gonçalo, Rio de Janeiro State, Brazil. The article analyzes the following information on families of 447 children that participated in two waves in a longitudinal study: social stratum, per capita family income, evolution in income over a three-year period, and psychosocial factors. The findings showed a 74.8% increase in the families' income, accompanied by an increase in the consumption of material assets and access to health services. This increase should not be interpreted as a guarantee of improved living and health conditions, since it was spent on basic products and needs that do not substantially affect the families' form of social inclusion. Psychosocial risk factors were frequent among the families, but decreased during the study period, which may either reflect the improved family situation or result from the later stage in child development. O objetivo deste artigo é avaliar os reflexos do recente crescimento econômico brasileiro sobre o rendimento monetário, o padrão de consumo familiar e os riscos em que vivem famílias da rede pública do Ensino Fundamental do Município de São Gonçalo, Rio de Janeiro, Brasil. São analisadas as seguintes informações sobre as famílias de 447 crianças que participaram de duas ondas de estudo longitudinal: estrato social, renda familiar per capita, evolução de renda no período e fatores psicossociais. Os resultados indicam incremento financeiro em 74,8% das famílias, acompanhado de aumento no consumo de bens materiais e no acesso a serviços de saúde. Esse crescimento não pode ser tomado como garantia de melhoria nas condições de vida e saúde, já que é gasto com a aquisição de produtos e necessidades básicas que não chegam a afetar substancialmente a forma de inserção social em que vivem as famílias. Os fatores de risco psicossociais mostraram-se frequentes, porém decrescentes nas famílias estudadas, o que pode refletir a melhoria da situação de vida familiar ou ser decorrente da etapa do desenvolvimento infantil.